PENGARUH KOMUNIKASI, KECERDASAN EMOSIONAL DAN IKLIM KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL TJAMPUHAN AND SPA UBUD - Ni Kadek Diah Ayu Apsari; Ni Nyoman Suryani; I Nyoman Mustika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Human resources are all the potentials possessed by humans in the form of thinking power, energy, skills, emotions, and other potentials that can be used effectively and efficiently to fulfill their own desires or to achieve organizational or company goals. Human resources are very vital organizational assets, therefore their roles and functions cannot be replaced by other resources. This study aims 1) to determine the effect of communication on employee performance, 2) to determine the effect of emotional intelligence on employee performance, and 3) to determine the effect of work climate on employee performance at Tjampuhan Hotel and Spa Ubud. This research was carried out at the Tjampuhan Hotel and Spa Ubud which is located at Jalan Raya Campuhan, Sayan, Ubud District, Gianyar Regency. The population used in this study were 70 employees at the Tjampuhan Hotel and Spa Ubud. Determination of the number of samples in this study was by the census method so that the entire population was sampled so that the number of samples in this study was 70 employees. Sources of data in this study are primary data and secondary data. Data collection techniques used in this study include observation, interviews, documentation and questionnaires. The data analysis technique used in this research is Multiple Linear Regression Analysis Technique, which is equipped with validity test, reliability test and classical assumption test, determination, F test and t test. The results of the analysis show that partially and simultaneously communication, emotional intelligence and work climate have a positive and significant effect on employee performance at the Tjampuhan Hotel and Spa Ubud. Suggestions that can be given from the results of this study are company management should communicate directly or face to face when carrying out work so that the message conveyed can be well received, besides that employees should be able to delay pleasure before completing the assigned task and employees should be able to solve problems without involving other people.